Criminal Justice Reform as HIV and TB Prevention in African Prisons - Todrys, Katherine W. (Public Library of Science, 2012)
Katherine Todrys and Joseph Amon argue for criminal justice system reforms in sub-Saharan Africa to reduce HIV and TB transmission in prisons and to guarantee detainees' human rights and health.